Analysis of Physico-Chemical Factors of Ramganga River Water in Bareilly District - Kumar, Sunil; Jain, Vikas (Journal for Research in Applied Sciences and Biotechnology, 2024)
The systematic study was carried out to determine the physico-chemical parameters of water samples of Ramganga River in Bareilly district. The rivers are an essential water resource and used for several purposes. The water quality of all fresh water ecosystems is assessed by the physico-chemical. Water samples were collected from 3 sites along the river and analyzed using standard methods in laboratory. The physico-chemical characteristics were studied and analyzed for a period of 6 months from April 2022 to September 2022. Various physico-chemical parameters such as Temperature, PH, transparency, total dissolved solids, total suspended solids, DO, FCO2, Carbonates, Bicarbonates, chlorides, Calcium, Magnesium, Total hardness of lake were estimated throughout the year.